The Lived Experience of Mindfulness in Adventure-Based Learning - Paul T. Stuhr; April L. Denny (Education Sciences, 2022)
Adventure-based learning (ABL) is an innovative K-12 instructional model that continues to be used in physical education to promote intrapersonal and interpersonal relationship skills. ABL incorporates low initiatives/cooperative activities coupled with periods of reflection to help enhance the likelihood of transferring intrapersonal and interpersonal relationship skills to other areas of K-12 student life. Mindfulness is a way of consciously and nonjudgmentally being aware of the present moment. Mindfulness practices (MPs) hold tremendous potential as a pedagogical tool in helping physical educators generate greater attention, equanimity, and compassion for themselves and their students. To further explore the impact of MPs for students, this study focused on undergraduate perception with regard to comprehension, practice, and demonstration of the possible benefits of MPs in three separate 16-week ABL teacher education courses. Specifically, we wanted to explore how students in the teacher education course conceptualized mindfulness as a phenomenon and how MPs played a part of their lived experience. Three themes were discovered: conceptualizing mindfulness, student interest with mindfulness, and perceived outcomes from mindfulness practices. The findings provide a deeper understanding of the participants’ meaning making of mindfulness, their overall buy-in and openness in using MPs, and the perceived benefits in using these contemplative practices.